Generic Medicine Substitution: A Cross-Sectional Survey of the Perception of Pharmacists in North-Central, Nigeria - Auta, Asa (Med Princ Pract, 2013)
OBJECTIVE: To investigate the views of pharmacists in North-Central Nigeria on generic medicines and generic substitution practices. SUBJECTS AND METHOD: A cross-sectional survey was conducted in 4 cities in North-Central Nigeria from April to June 2012 among 330 pharmacists in hospital and community pharmacy settings, recruited through a convenience sampling strategy. Data were collected using a prevalidated self-administered questionnaire and entered into SPSS version 16.0 software to generate descriptive statistics. Binary logistic regression was conducted to determine the demographic predictors of preference for generic substitution among respondents. RESULTS: The response rate was 46.7% (n = 154). Eighty-four (54.5%) respondents reported that generic medicines were not of equivalent quality to branded ones. There was no significant difference (p > 0.05) in the perception of respondents regarding the quality of imported generic medicines over locally manufactured ones. While 143 (92.9%) respondents supported generic substitution practices, 105 (68.2%) would prefer to recommend generic medicines over branded ones. Hospital pharmacists were more likely (OR = 2.6; 95% CI 1.2-5.8) than community pharmacists to recommend generic medicines. One hundred and fifty-three (99.4%) respondents would support the implementation of a future generic substitution right for pharmacists in Nigeria. CONCLUSION: The present study showed a high support for generic substitution and future generic substitution rights for pharmacists in Nigeria.